Dynamics of endogenous intoxication indicators in condition of acute blood loss complicated by ischemia-reperfusion of the limb, and their correction by carbacetam - Strelbytska, I.; Hudyma, A. (Journal of Education, Health and Sport, 2020)
Introduction. In the structure of injuries from gunshot wounds dominate the limb injuries that are often complicated by massive bleeding from the main vessels. The only means of rescue on the battlefield is a timely application of a tourniquet. This ensures complete exsanguination of the limb. The duration of exsanguination should not exceed 2 hours. It is proved that in conditions of acute blood loss complicated by ischemia-reperfusion of the limb, there are prerequisites for the development of dysfunction of internal organs, which in turn exacerbates dysmetabolic and functional disorders, stimulates endotoxicosis and may be complicated by multiple organ failure. However, the patterns of formation of the syndrome of endogenous intoxication in the conditions of ischemia-reperfusion of the limb, acute blood loss and their combinations have not been studied. There are no data on the effect of Carbacetam on these processes. It is known that Carbacetam has proven itself to reduce the manifestations of dysfunction of internal organs in the conditions of ischemic-reperfusion syndrome of the limb. The objective of research: To establish the dynamics of endogenous intoxication in the conditions of ischemia-reperfusion of the limb, acute blood loss and their combination. To evaluate the effectiveness of Carbacetam in the correction of identified abnormalities. Materials and methods. The experimental studies were conducted on 108 white nonlinear male rats weighing 200-220 g, which were housed in standard vivarium conditions. All animals were divided into five groups: control and four experimental. Under thiopental-sodium anesthesia in the first experimental group was simulated ischemia-reperfusion of the limb, in the second – acute blood loss, and in the third – these injuries were combined. In the fourth experimental group, animals with acute blood loss and ischemia-reperfusion of the limb were intraperitoneally administered Carbacetam at a dose of 5 mg per kilogram of animal weight. After 1 and 2 hours, as well as after 1, 7 and 14 days in the blood serum was determined the content of middle-mass molecules (MMM254, MMM280). The results and discussion. It was found that ischemia-reperfusion of the limb in comparison with the control group is accompanied by a significant increase of the MMM254 fraction in the blood serum content. From the first hour of the experiment with a maximum after 1 day and normalization of the index up to 14 days. The content in the blood serum of the MMM280 fraction became significantly higher, from the control only after 1 day with subsequent normalization in the following terms of the experiment. After simulation of acute blood loss, both studied fractions of MMM increased from 1 hour of the experiment, reached a maximum after 1 day and did not return to the control level after 14 days. For the first time it was found that two-hour ischemia-reperfusion of the limb significantly aggravates the course of acute blood loss, which revealed a significantly higher content in the serum of fractions MMM254 and MMM280 compared to other experimental groups in almost all periods of the experiment. Due to the use of Carbacetam, the content of both studied fractions of MMM in the serum compared with animals without correction was significantly reduced after 7 and 14 days of the experiment. Although the studied parameters did not return to the level of the Carbacetam control group, it can be considered a pathogenetically justified means of reducing the level of endotoxicosis in the conditions of ischemia-reperfusion of the limb and acute blood loss. Conclusions. Simulation of limb ischemia-reperfusion is accompanied by accumulation of MMM254-280 fractions with a maximum after 1 day of the experiment and normalization up to 14 days. Acute blood loss causes an increase in the serum content of fractions MMM254-280 from 1 hour of the experiment, which up to 14 days do not reach the level of control. The detected disorders are significantly exacerbated after a combination of acute blood loss and ischemia-reperfusion of the limb. The use of Carbacetam in comparison with animals without correction is accompanied by a significant decrease in the content of MMM254-280 fractions in the serum after 7 and 14 days of the experiment.